2022
DOI: 10.3390/foods11152320
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Quality Evaluation for Medicinal and Edible Ziziphi Spinosae Semen before and after Rancidity Based on Traditional Sensory, Physicochemical Characteristics, and Volatile Compounds

Abstract: To comprehensively evaluate the quality of medicinal and edible Ziziphi Spinosae Semen (ZSS, the dried ripe seeds of Ziziphus jujuba var. spinosa) before and after rancidity during storage, some indicators including traditional sensory properties, physicochemical characteristics, and volatile compounds were analyzed. As a result, compared with the normal samples, the rancid samples of ZSS produced a darker color, a bitter taste, and an irritating odor, increased moisture content, electrical conductivity, fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
(84 reference statements)
1
2
0
Order By: Relevance
“…Jujuboside A was found to be the predominant compound in FZSS. Further analysis found that sanjoinenine was more abundant in FZSS than in RZSS, which is consistent with previous research by HPLC and GC studies 39 . Moreover, FZSS exhibited superior sedative properties compared to RZSS, which could be explained from the perspective of spatial chemistry 40 .…”
Section: Discussionsupporting
confidence: 92%
“…Jujuboside A was found to be the predominant compound in FZSS. Further analysis found that sanjoinenine was more abundant in FZSS than in RZSS, which is consistent with previous research by HPLC and GC studies 39 . Moreover, FZSS exhibited superior sedative properties compared to RZSS, which could be explained from the perspective of spatial chemistry 40 .…”
Section: Discussionsupporting
confidence: 92%
“…Cynaroside (Cy) is the 7-O-glucoside of luteolin, a avone (subclass of avonoids) naturally occurring in several plant species, including Lonicera caerulea L. (honeysuckle) (Bouyahya et al 2023). Several studies have reported that Cy has numerous pharmacological properties, such as antibacterial, antifungal, antileishmanial, antioxidant, hepatoprotective, antidiabetic, anti-in ammatory, and anticancer properties (Bouyahya et al 2023;He et al 2023;Liu et al 2023). Although Cy has good biological activity, its application is limited due to its low extraction e ciency and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being medicinal, it is also commonly used in Foods 2023, 12, 3126 2 of 25 healthy food, cosmetics, wines, and tea for its specific activities and unique aroma [16]. With the transformation in medical purposes and health perspectives, people prefer to prevent disease through diet in their daily life [17]. Honeysuckle, as a medical and edible substance, has gained great popularity among consumers in the healthcare industry [18].…”
Section: Introductionmentioning
confidence: 99%